Innate immune sensing and response - Beutler, Bruce (Henry Stewart Talks, 2009)
Sensing infection is essential to the initiation of an immune response, The innate immune system senses signature molecules made by microbes using a conserved set of germline-encoded receptors, This receptor family (the Toll-like receptors) was first understood when a mutation that abolished lipopolysaccharide (LPS) sensing was positionally cloned in mice, In Drosophila a homologous receptor is also used to detect infection, and still another receptor activates a pathway evocative of the tumor necrosis factor (TNF) pathway in mammals, Further work in mammals has depended upon gene targeting and also forward genetic work, which has revealed many of the components of the TLR signaling apparatus, Forward genetics has also allowed us to see how many genes (and what kinds of genes) are important for resisting an infection in vivo